Chronic post-dural puncture headache–a serious and underrated complication following lumbar puncture: a cohort study - Kraus, Luisa Mona; Häni, Levin; El Rahal, Amir; Vasilikos, Ioannis; Fariña Nuñez, Mateo Tomas; Volz, Florian; Urbach, Horst; Lützen, Niklas; Ulrich, Christian; Beck, Jürgen; Fung, Christian (Frontiers in Neurology, 2024)
BackgroundPost-dural puncture headache (PDPH) is still mostly regarded a minor complication after lumbar puncture. In the International Classification of Headache Disorders (ICHD)-3 headaches lasting longer than 14 days or persisting after epidural blood patch (EBP) are not even considered. We illustrate that there may be many patients with persisting headaches and a large disease burden.MethodsIn a retrospective, single center analysis from 04/2018 to 03/2022 we assessed patients with a dural puncture and orthostatic headache of >14 days duration, resistant to one or more EBPs. Socioeconomic factors and individual patient history were assessed by a specifically designed questionnaire.ResultsWe included 30 patients with a mean age of 36.4 (±10.6) years. The median duration of acute inpatient care was 31 (Interquartile ratio (IQR) = 32) days and of sick leave 381 (IQR = 666.3) days. Patients consulted a median of 5 (IQR = 6.5) different physicians/ institutions due to chronic post-dural puncture headache (cPDPH). All patients reported major negative impact of cPDPH on their social and work life.ConclusionDespite long hospitalizations and a profound impairment of social and work lives cPDPH was neglected and underrated in all patients. We conclude that cPDPH needs to be considered and might be an underreported, severe condition which requires further prospective studies.